Avaliação da capacidade antioxidante e aspectos nutricionais na hanseníase - Vázquez, Cecília Maria Passos (2012)
Leprosy is an infectious and contagious Mycobacterium Leprae affects mainly the skin and nerves causing, in many cases, severe deformities, a reason for a strong social stigma. However, only 5% of people who come in contact with these bacilli develop the disease. Some factors influence the individual's resistance to M. leprae, including, nutrition, genetics and the human immune response, which may be affected by these two factors. However, few studies evaluate the effect of nutritional status in altering the immune response for this disease. Objective: To evaluate nutritional parameters and antioxidant capacity in patients with leprosy. Methods: This is cross-sectional study with comparison groups developed at the Dermatology Clinic of the University Hospital in the state of Sergipe from January 2010 to December 2011. The participants were 39 patients with the disease and 34 healthy subjects of both sexes. Anthropometric, dietary and blood data for the evaluation of total antioxidant capacity (CAOT) and superoxide dismutase (SOD) were collected. Results: The study showed that 53.8% of participants had inadequate values for BMI, TSF and AMC, in the patients with the disease 63.2% of women were overweight. The majority of the population had inadequate intakes of vitamins A, E, and 100% had inadequate intake of vitamin D; this vitamin is evolved in microbial activity of the macrophages and in the immune regulatory response evolution. CAOT concentrations were higher in the patients with the disease compared to the control group (p = 0.0003), no difference was observed in SOD values between both groups. Patients with the disease showed the relative Fe / CAOT (p = 0.003) and lipids / CAOT (p = 0.0001) lower than those of controls, which shows that the total antioxidant capacity overlaps the oxidant nutrients. Conclusion: The study population, independent of disease, presents malnutrition. Overweight and inadequate intake of foods compromise the balance of the oxidant / antioxidant status and inflammatory response. CAOT is higher in the patients groups and can be involved in the inhibition of the microbial mechanisms that can affect the clinical evolution of the disease.